2007
DOI: 10.1016/j.cmet.2006.12.006
|View full text |Cite
|
Sign up to set email alerts
|

Gapex-5, a Rab31 Guanine Nucleotide Exchange Factor that Regulates Glut4 Trafficking in Adipocytes

Abstract: Insulin stimulates glucose uptake by promoting translocation of the Glut4 glucose transporter from intracellular storage compartments to the plasma membrane. In the absence of insulin, Glut4 is retained intracellularly; the mechanism underlying this process remains uncertain. Using the TC10-interacting protein CIP4 as bait in a yeast two-hybrid screen, we cloned a RasGAP and VPS9 domain-containing protein, Gapex-5/RME-6. The VPS9 domain is a guanine nucleotide exchange factor for Rab31, a Rab5 subfamily GTPase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
104
1
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(109 citation statements)
references
References 59 publications
3
104
1
1
Order By: Relevance
“…The docking of GLUT4 vesicles with the plasma membrane appears to require the Exocyst complex that is formed from the assembly of 8 distinct proteins [29][30][31][32]. In the case of GLUT4, the Exo70, Sec6 and Sec8 protein component of this complex redistribute to the plasma membrane in response to insulin [29] These events are triggered by the insulin activation of a small GTP binding protein TC10 that recruits Exo70 with Sec6 and Sec8 to lipid raft microdomains in the plasma membrane [33,34]. Moreover, Sec8 associates with the PDZ domain of SAP97 a MAGUK (membrane-associated guanylate kinase) family member that is recruited along with Sec8 [33].…”
Section: Glut4 Vesicle Docking and Plasma Membrane Fusionmentioning
confidence: 99%
See 1 more Smart Citation
“…The docking of GLUT4 vesicles with the plasma membrane appears to require the Exocyst complex that is formed from the assembly of 8 distinct proteins [29][30][31][32]. In the case of GLUT4, the Exo70, Sec6 and Sec8 protein component of this complex redistribute to the plasma membrane in response to insulin [29] These events are triggered by the insulin activation of a small GTP binding protein TC10 that recruits Exo70 with Sec6 and Sec8 to lipid raft microdomains in the plasma membrane [33,34]. Moreover, Sec8 associates with the PDZ domain of SAP97 a MAGUK (membrane-associated guanylate kinase) family member that is recruited along with Sec8 [33].…”
Section: Glut4 Vesicle Docking and Plasma Membrane Fusionmentioning
confidence: 99%
“…Expression of a dominant-interfering CIP4/2 mutant inhibited insulin-stimulated GLUT4 translocation. Further studies using CIP4 as bait, identified Gapex-5, a RasGAP and VPS9 domain-containing protein that functions as a guanine nucleotide exchange factor (GEF) for Rab31, a Rab5 subfamily GTPase that involved in trans-Golgi network (TGN)-to-endosome trafficking [34]. Insulin recruited the CIP4/Gapex-5 complex to the plasma membrane, thereby decreasing Rab31 activity.…”
Section: Insulin Signaling Leading To Glut4 Translocationmentioning
confidence: 99%
“…Gapvd1, is an activator of the early endosome regulator protein Rab. It regulates vesicular trafficking processes such as endocytosis of activated transmembrane proteins and exocytosis of GLUT4 vesicles (Hunker et al, 2006;Lodhi et al, 2007). Recent studies have shown that it can regulate EGFR endocytosis and degradation independently of Rab5 function (Su et al, 2007).…”
Section: Vav2 Knockdown Affects Egfr Degradationmentioning
confidence: 99%
“…A number of observations have accumulated that describe the possible linkages between insulin receptor tyrosine kinase-derived signaling components and heterotrimetic G-proteins (19). G-proteins participate in insulin-stimulated translocation of glucose transporter GLUT4 in 3T3-L1 adipocytes (20,21). In addition, Ptx can alter the action of insulin (22).…”
Section: Discussionmentioning
confidence: 99%